Illicit Sex, Karma and Karmic Discredit in Kunle Afolayan’s Citation - Abiodun Olukayode Tairu (Randwick International of Social Science Journal, 2024)
Karmic discredit and law of Karma is a belief system in Hinduism and Buddhism. It is a force created by a person’s actions which to a degree determines what that person’s next life or his fate in the current life will be or look like. This belief is widely held on to that many people believe the cause of good or bad things that happens to a person has to do with karma. The catastrophic and astronomic fall of Professor Lucien N’Dyare from his lofty height and enviable academic pedestals is tagged to karmic discredit; not as a result of the damage done to Moremi but as a result of the sexual abuse done to Diatta, a promising young lady and daughter of Mr Cardosa who he deceived to bed with a failed offer of a scholarship which later haunted him to fall at Moremi’s feminist whims. The study adopts Hooks (2000) Feminist theory to interrogate illicit sex and karmic discredit in Kunle Afolayan’s Citation. As Hooks (2000) puts it, feminism is a movement to end sexism, sexist exploitation and oppression. This is exactly what the protagonist in the movie Moremi Oluwa was designed to achieve. She was to liberate female students from the clog of male lecturers who demand sex for grades. Finding reveals that Professor Lucien N’Dyare in the movie made an effortless attempt to sexually harass Moremi Oluwa right in his office, and at a later time, made another attempt to rape her in his residence after he had successfully schemed out a party that lured Moremi Oluwa to his trapped chamber one evening.